GLOCALIZATION, EMBEDDING, ANCHORING: ON THE COGNITIVE IMPACT AND EXPERIENCE OF GLOBALIZATION (Glocalism: Journal of Culture, Politics and Innovation, 2025)
This essay discusses globalization and glocalization as crucially important concepts for the Social Sciences and Humanities, thereby distinguishing between globalization/ glocalization as research methodology (hermeneutics) and as historical process unfolding through time. For many SSH scholars the term globalization evokes historical processes that likewise spanned the globe and were (apparently) directed from above, such as imperialism, Westernisation and modernisation. Defining globalization as glocalization, which it is by nature, might help to overcome this (incorrect) association and make it into an important instrument of the (decolonial) SSH toolbox. After discussing the content of the Handbook of Culture and Glocalization, edited by Victor N. Roudometof and Ugo Dessì (2022), to show what glocalization entails and how the concept is fruitfully used over a variety of fields already, I focus on the idea of “arrival” as a next step in our research agenda. Glocalization, I argue, is very much about the impact of globalization, in local contexts, in cognitive terms of experience. Increasing global dynamics demand embedding practices to make globalization work on the ground, in the lives of people, as glocalization. To a successful outcome of these inherently difficult processes, often fraught with anxiety and friction, anchoring is key.
Keywords: globalization; glocalization; embedding; anchoring; experience